The Effect of Project-Based Differentiation Approach on Students' Civic Engagement in Social Studies Learning at SMPN 4 Subang - Siti Sangadah; Lili Halimah; Khaerul Syobar (EDUKASI, 2026)
This study aims to examine the effect of a project-based differentiated learning approach on students’ civic engagement in social studies learning. The study employed a quantitative method with a predictive correlational design. The population consisted of 1,146 students from grades VII, VIII, and IX at SMP Negeri 4 Subang, with a sample of 297 students selected using proportionate stratified random sampling. Data were collected through structured Likert-scale questionnaires measuring project-based differentiated learning and civic engagement. The instruments were validated through expert judgment and item analysis, and their reliability was confirmed using Cronbach’s Alpha. Data analysis included descriptive statistics, prerequisite tests (normality and heteroscedasticity), and simple linear regression analysis. The results show that the implementation of project-based differentiated learning is categorized as good and has a significant positive effect on students’ civic engagement (β = 0.901; p < 0.05). The strength of the relationship is also supported by a strong correlation coefficient (r = 0.740). Furthermore, the effect is consistently observed across all dimensions of civic engagement, including active participation, social responsibility, democratic decision-making, and civic action. These findings indicate that integrating differentiated instruction with project-based learning creates a more adaptive, contextual, and student-centered learning environment that promotes meaningful social involvement. In conclusion, project-based differentiated learning serves as an effective instructional approach to enhance students’ civic engagement in social studies. This approach is recommended for fostering not only academic achievement but also students’ social awareness and responsible citizenship behavior.